Navigated TMS in the ICU: Introducing Motor Mapping to the Critical Care Setting - Schramm, Severin; Haddad, Alexander F.; Chyall, Lawrence; Krieg, Sandro M.; Sollmann, Nico; Tarapore, Phiroz E. (Brain sciences, 2020)
Navigated transcranial magnetic stimulation (nTMS) is a modality for noninvasive cortical mapping. Specifically, nTMS motor mapping is an objective measure of motor function, offering quantitative diagnostic information regardless of subject cooperation or consciousness. Thus far, it has mostly been restricted to the outpatient setting. This study evaluates the feasibility of nTMS motor mapping in the intensive care unit (ICU) setting and solves the challenges encountered in this special environment. We compared neuronavigation based on computed tomography (CT) and magnetic resonance imaging (MRI). We performed motor mappings in neurocritical patients under varying conditions (e.g., sedation or hemicraniectomy). Furthermore, we identified ways of minimizing electromyography (EMG) noise in the interference-rich ICU environment. Motor mapping was performed in 21 patients (six females, median age: 69 years). In 18 patients, motor evoked potentials (MEPs) were obtained. In three patients, MEPs could not be evoked. No adverse reactions occurred. We found CT to offer a comparable neuronavigation to MRI (CT maximum e-field 52 ± 14 V/m vs. MRI maximum e-field 52 ± 11 V/m; p = 0.6574). We detailed EMG noise reduction methods and found that propofol sedation of up to 80 mcg/kg/h did not inhibit MEPs. Yet, nTMS equipment interfered with exposed pulse oximetry. nTMS motor mapping application and use was illustrated in three clinical cases. In conclusion, we present an approach for the safe and reliable use of nTMS motor mapping in the ICU setting and outline possible benefits. Our findings support further studies regarding the clinical value of nTMS in critical care settings.